First immature of the New World treehopper Campylocentrus nigris Funkhouser, 1930 (Hemiptera, Membracidae, Centrotinae, Boocerini) and biological notes from Costa Rica - Andrey J. Peraza-Sánchez; Stuart H. McKamey (ZooKeys)
The last immature stage of the New World treehopper Campylocentrus nigris Funkhouser, 1930 is described for the first time. Detailed figures of the adult are also provided, as well as new records, data on its behavior, distribution for Costa Rica, and host plants. Its host plant, chayote, is an important food staple locally and also a U.S. import. Panama is a new country record for the species.